The Effect of Knowledge and Perceptions on the Prospect of Using Biofuel-Based Alternative Energy Sources - Anggereini, Evita; Aina, Mia; Nainggolan, Rina Aprianti (LPPM Undiksha, 2022)
Indonesia's energy needs each year increase in line with economic growth and population. Indonesia still needs to work on achieving its development targets in the energy sector to date. Dependence on fossil energy, especially petroleum, is still high to meet domestic energy consumption. Non-renewable energy reserves such as oil, natural gas, and coal are very worrying because they run low. The urgency in this study is very important because there are rarely studies that compare the Knowledge and Perceptions about the Prospects of Utilizing Biofuel-Based Alternative Energy Sources. This study aims to analyze the effect of knowledge and perceptions about the Prospects of Utilizing Biofuel-Based Alternative Energy Sources. This research method is a mixed method, with the sampling technique in this study being multistage random sampling. The number of respondents as a sample is 100 respondents. The data collection instruments used were in the form of questionnaires, in-depth interviews, and documentation. Data analysis in this study is divided into descriptive statistical testing (mean, median, min, and max) and inferential (simple regression). The regression test results show an influence of Knowledge and Perception about the Prospects of Utilizing Biofuel-Based Alternative Energy Sources.